A Foucauldian Reading: Power in Awakening by Kate Chopin - Narges Raoufzadeh; Fatemeh Sadat Basirizadeh; Shiva Zaheri Birgani (Budapest International Research and Critics University, 2020)
This paper traces Foucault’s notion of power in Kate Chopin’s The Awakening. The writers bring into the light, different aspects of a woman’s position in the society of late nineteenth-century America. Paper looks at private and social conditions of women, using Foucault’s ideology of power, and discuss the reactions of Chopin’s protagonist in relation to her actions towards the workings of power in her life. With a close analysis of the novel based on Foucault’s ideology of power, researchers discuss the workings of power in the protagonist’s married and social life, including her efforts to set herself free from this power and her process of resistance analyzed according to Foucault’s theory. The research comes to the conclusion that the impossibility of acting outside power, the possibility of resisting power from within and Foucault’s “Care of the self” as the only way to traverse the power-defined failed of possible actions. Paper shows that, Chopin’s protagonist does not resist patriarchy based on Foucault’s methods and her actions towards power do not lead to any effective ending.